مفهوم الجهاد عند سيد قطب في ظلال القران ومدى أثره في الجماعة الإسلاميّة في إندونيسيا - Aulia Naufal
A research conducted through historical approach as methodology, analysis and deductive method, regarding Jihad definition according to Sayyid Qutb and the influence on Jamaah Islamiyyah in Indonesia. This paper examine the history and Sayyid Qutb’s understanding in his book: “In the Shade of The Qur’an/Fi Zilal Quran” as well as explanation by some contemporary scholars on jihad as whole and specially in addition, elaboration Jamaah Islamiyah history and member’s opinion on jihad meaning, thru their movement in applying current context of jihad as many people view as a terrorist act, furthermore dakwah including jihad by Jamaah Islamiyah. In order to collect the data on Sayyid Qutb and contemporary scholar’s thought, also the members of Jamaah Islamiyah about their history and definition on jihad, the writer conducting research through literatures concerning the history and their movement and orientalist literatures discussing about them. The final research shows that the influence Sayyid Qutb understanding on jihad in Jamaah Islamiyah as claimed by westerns is not proven directly, through analysis derived from literatures and articles. This shows that Sayyid Qutb understanding on jihad is right and precise, thus we need to be able to comprehend that he wrote on the definition on jihad attentively, the Jamaah Islamiyah in Indonesia is a group striving to establish Islamic state rules in Indonesia via acting on movements related to terrorism such as illegal military exercise, bombing government building, suicide bombing etc., this group eventually banned by Indonesian government as their existence is extremely dangerous to the society.